2016
DOI: 10.1071/an14771
|View full text |Cite
|
Sign up to set email alerts
|

A promising and simple method to quantify soil/manure mixing on beef feedlot pens

Abstract: Abstract. On beef cattle feed pen surfaces, fresh and decayed manure is mixed with base rock or soil (base). Quantifying this mixing has beneficial applications for aspects including nutrient and greenhouse gas budgeting. However, no practical methods exist to quantify mixing. We investigated if measuring element concentrations in: (A) fresh manure, (B) base material, and (C) pen manure offers a promising method to quantify manure/base mixing on pen surfaces. Using three operational beef feedlots as study site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Apparent water losses due to evaporation over the 45‐d period from the entire pan, as determined by weekly weighing of the pans, were 4.8, 6.9, 9.2, 11.6, and 22.5 kg for TRT 1, 2, 3, 4, and 5, respectively. These calculated water losses do not account for mass loss due to biological decay or ammonia volatilization and as such may be inflated (Pratt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Apparent water losses due to evaporation over the 45‐d period from the entire pan, as determined by weekly weighing of the pans, were 4.8, 6.9, 9.2, 11.6, and 22.5 kg for TRT 1, 2, 3, 4, and 5, respectively. These calculated water losses do not account for mass loss due to biological decay or ammonia volatilization and as such may be inflated (Pratt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Volumetric methane yield of 0,13-0,16 L CH 4 /g VS-fed were found in Pratt's et al (2016) study. Other studies have (IPCC, 2006) reported 0,17 L CH 4 /g VS-fed and variation of 0,07-0,28 L CH 4 /g VS-fed (Gopalan et al 2013).…”
Section: Biogas and Methane Yieldmentioning
confidence: 49%